DUKUNGAN MANAJEMEN PUNCAK SEBAGAI PEMODERASI PENGARUH KAPASITAS SUMBER DAYA MANUSIA DAN TEKNOLOGI INFORMASI PADA IMPLEMENTASI SIPKD DI PEMERINTAH KOTA DENPASAR - Trisna Dewi, Sang Ayu Nyoman; Badera, Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017DO - 10.24843/EEB.2017.v06.i07.p08, 2017)
Information technology has become a major part of an organization. To realize good governance, one of which can be done by continuing to make improvements in the area of ??financial management and implement applications Fiscal Management Information System (SIPKD). The success of this application is not separated from the quality of human resources, information technology and management support. This research was conducted using a survey method with questionnaire technique. The population in this research were 166 respondents, consisting of employees of the finance department and agency heads in Denpasar government as much as 70 respondents with a purposive sampling techniques and models of multiple regression analysis and regression analysis moderation. The result is the capacity of human resources and information technology has positive effect on the implementation of financial management information system. Top management support strengthening the influence of human resource capacity and the implementation of information technology in government SIPKD Denpasar.
Keywords: Capacity of Human Resources, Information Technology, Top Management Support and Implementation Regional Financial Management Information System (SIPKD).